2023
DOI: 10.1111/aos.15711
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of biometry in patients with meibomian gland dysfunction before and after vectored thermal pulsation therapy: A randomized, controlled trial

Andreas Schlatter,
Stefan Palkovits,
Manuel Ruiss
et al.

Abstract: PurposeTo evaluate the effect of vectored thermal pulsation therapy (VTPT) on the repeatability of biometry readings of two different optical biometers in patients with meibomian gland dysfunction (MGD).MethodsPatients affected by MGD were included in this prospective, randomized, controlled, investigator‐masked study. One eye was randomized to VTPT (LipiFlow®, Johnson & Johnson), and the contralateral eye served as a control. Three visits were scheduled at baseline, 2 weeks and 3 months after the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Three studies evaluated the effect of pre-operative LipiFlow treatment on intraocular lens (IOL) selection. One study of 31 patients (29 eyes) with MGD concluded that LipiFlow improved tear film parameters but had negligible effect on spherical IOL selection [ 63 ]. In contrast, two studies of 29 patients with MGD (36 eyes) concluded that LipiFlow treatment stabilized the tear film and improved the accuracy of the IOL power calculations especially the keratometry readings [ 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies evaluated the effect of pre-operative LipiFlow treatment on intraocular lens (IOL) selection. One study of 31 patients (29 eyes) with MGD concluded that LipiFlow improved tear film parameters but had negligible effect on spherical IOL selection [ 63 ]. In contrast, two studies of 29 patients with MGD (36 eyes) concluded that LipiFlow treatment stabilized the tear film and improved the accuracy of the IOL power calculations especially the keratometry readings [ 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies evaluated the safety of LipiFlow when treating MGD in patients with cataract (235 patients, 229 eyes), and the data are presented in Table 6 . There were no AEs, pain, or safety concerns related to LipiFlow treatment [ 63 , 66 , 67 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation